FOLIAR SYMPTOMS RECOVERY: DEVELOPING SCORING TECHNIQUE FOR ASSESSMENT OF SOYBEAN RESISTANCE TO CPMMV (COWPEA MILD MOTTLE VIRUS) - Siti Zubaidah; Heru Kuswantoro (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2016)
Soybean is a commodity that has an important role as the source of protein, but its production is affected by various factors including disease. CpMMV (Cowpea mild mottle virus) is one of the most damaging viruses that cause soybean disease. CpMMVs belong to the group of Carlavirus that are transmitted by whitefly (Bemisia tabaci). The use of CpMMV resistant plants as biological control can prevent viral diseases. Indonesia has many soybean germplasm from many regions and introduction from other countries that need to be evaluated for CpMMV. The assessment technique for soybean resistance to CpMMV is not available yet, but it is still based on other virus diseases. The specific assessment of plant resistance is important because some diseases can cause certain symptoms, depends on the resistance and the kinds of plants that are infected. This paper presents the assessment technique for soybean resistance to CpMMV infection, which can be used for various purposes and studies. One of the benefits is to find out soybean resistance to CpMMV or other objectives. This resistance assessment is not only based on leaves symptoms, but also based on the phenomenon of foliar symptoms recovery.